Penguatan Pendidikan Karakter Melalui Pendidikan Agama Islam di Era Globalisasi - Wisiyanti, Rahma Ayu (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Character education is an important aspect in the formation of individual personality, especially in the era of globalization that demands strong moral and ethical values. This study aims to examine how Islamic religious education can be a solution in strengthening character education in the era of globalization. This study uses a literature study method by collecting data from various literature sources, including books, journal articles, and documents related to the Islamic religious education curriculum. The results of the study indicate that Islamic religious education not only functions to teach norms and values, but also as a means to shape students' character through daily life practices. The discussion outlines the important role of religious education in creating individuals with noble character and the challenges faced in its implementation. The conclusion emphasizes that the integration of character values ​​in Islamic religious education is very important for building a society with integrity in the midst of globalization.